DIALEKTIKA NILAI PENDIDIKAN ISLAM DAN MODERNITAS DALAM KONSTRUKSI GENDER PADA ORGANISASI MAHASISWA ISLAM - Bq Ditia Widari; Ahmad Sulhan; Mira Mareta; Maimun Maimun; M. Sobry; Hilmiati Hilmiati (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT This study is motivated by the paradox between the normative commitment of Islamic student organizations to gender equality and organizational social practices that still demonstrate gender bias tendencies. The study aims to analyze the dialectic between Islamic educational values and modernity in shaping gender construction within the Indonesian Islamic Student Movement (PMII) at UIN Mataram. This research employed a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation studies involving PMII administrators and members. Data analysis used the interactive model of Miles, Huberman, and Saldana through data condensation, data display, conclusion drawing, and verification. The findings reveal that PMII serves as a dialectical space that integrates Islamic educational values and modernity within its cadre system, organizational culture, and leadership practices. Aswaja values such as tawazun, tasamuh, ta’adul, and i’tidal form the basis for developing a contextual and moderate understanding of gender. Modernity is reflected through critical culture, gender education, meritocracy, and the strengthening of women’s intellectual capacities. However, patriarchal culture still influences organizational social practices, particularly in stereotypes toward women’s leadership, gender-biased division of labor, and the low participation of women in strategic organizational spaces. The study concludes that gender construction in PMII is formed through a dynamic negotiation process between Islamic educational values and modernity, resulting in a dialogical, moderate, and evolving understanding of gender. ABSTRAK Penelitian ini dilatarbelakangi oleh adanya paradoks antara komitmen normatif organisasi mahasiswa Islam terhadap kesetaraan gender dengan praktik sosial organisasi yang masih menunjukkan kecenderungan bias gender. Penelitian ini bertujuan menganalisis dialektika nilai pendidikan Islam dan modernitas dalam membentuk konstruksi gender pada Pergerakan Mahasiswa Islam Indonesia (PMII) di UIN Mataram. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi terhadap pengurus serta kader PMII. Analisis data dilakukan menggunakan model interaktif Miles, Huberman, dan Saldana melalui tahapan kondensasi data, penyajian data, penarikan simpulan, dan verifikasi. Hasil penelitian menunjukkan bahwa PMII menjadi ruang dialektik yang mempertemukan nilai pendidikan Islam dan modernitas dalam sistem kaderisasi, budaya organisasi, dan praktik kepemimpinan kader. Nilai-nilai Aswaja seperti tawazun, tasamuh, ta’adul, dan i’tidal menjadi landasan dalam membangun pemahaman gender yang moderat dan kontekstual. Modernitas tercermin melalui budaya kritis, pendidikan gender, meritokrasi, dan penguatan kapasitas intelektual perempuan. Namun, budaya patriarki masih memengaruhi praktik sosial organisasi, terutama dalam stereotip kepemimpinan perempuan, pembagian kerja berbasis gender, dan rendahnya partisipasi perempuan dalam ruang strategis organisasi. Penelitian ini menyimpulkan bahwa konstruksi gender di PMII terbentuk melalui proses negosiasi dinamis antara nilai pendidikan Islam dan modernitas sehingga menghasilkan pemahaman gender yang dialogis, moderat, dan terus berkembang.